2022
DOI: 10.1155/2022/3489785
|View full text |Cite
|
Sign up to set email alerts
|

Labeling of Genetically Modified (GM) Foods in Peru: Current Dogma and Insights of the Regulatory and Legal Statutes

Abstract: The COVID-19 pandemic has affected and afflicted human lives and been a transformative catalyst leading to closure of many companies, disrupting mental health, and reducing access to food and exacerbating food insecurity. This presents an opportunity to reflect on and examine genetically modified (GM) foods and their effective legislative regulation for the benefit of consumers. This review presents a detailed analysis of GM foods’ regulation in Peru and the analysis of certain specific cases that show the nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 89 publications
(63 reference statements)
0
8
0
Order By: Relevance
“…The potential of plant-based nanoparticles to treat different cancers is being extensively studied and well reviewed [76] and the application of silver and gold nanoparticles to treat cancers is a very active area of research investigations [76][77][78][79][80]. Recent studies revealed that the use of the various metallic nanoparticles in medical sciences has various applications, such as bio-imaging [81][82][83][84], bio-sensing [85][86][87], and drug delivery [88][89][90] of nutraceuticals [23,26,[91][92][93][94][95][96][97][98][99], and pharmaceuticals [17,20,31,100], which could affect disposition [13,24,25,[27][28][29][30]32,33,[101][102][103][104][105][106][107]…”
Section: Introductionmentioning
confidence: 99%
“…The potential of plant-based nanoparticles to treat different cancers is being extensively studied and well reviewed [76] and the application of silver and gold nanoparticles to treat cancers is a very active area of research investigations [76][77][78][79][80]. Recent studies revealed that the use of the various metallic nanoparticles in medical sciences has various applications, such as bio-imaging [81][82][83][84], bio-sensing [85][86][87], and drug delivery [88][89][90] of nutraceuticals [23,26,[91][92][93][94][95][96][97][98][99], and pharmaceuticals [17,20,31,100], which could affect disposition [13,24,25,[27][28][29][30]32,33,[101][102][103][104][105][106][107]…”
Section: Introductionmentioning
confidence: 99%
“…The holding of the release of GM crops to the market prevents the economic benefits that countries can attain through their production. However, a solution has been developed towards such issue is by labelling of the GM crops for the market sales ( Delgado-Zegarra et al., 2022 ). Such labelling’s allow for the consumer’s sovereignty as the people have the fundamental right to know what food they are consuming and about the processes involved in its production ( Yeh et al., 2019 ).…”
Section: Potential Solutions For Growing Commercializing and Incorpor...mentioning
confidence: 99%
“…The economical aspect of GM crops faces the issue of intellectual property rights ( Delgado-Zegarra et al., 2022 ). The producers of GM crops have used terminator technology to protect their seeds and reduce the gene flow.…”
Section: Perspectives On the Criticisms Of Gm Crops Incorporation Int...mentioning
confidence: 99%
See 1 more Smart Citation
“…Food choice is influenced by consumption patterns [ 1 , 2 , 3 , 4 ] and eating and cooking behaviors, which have changed dramatically in 20 years, partially influenced by rapid urbanization [ 5 ] and increased awareness of nutritional labeling related to the presence of transgenics [ 2 ]. Furthermore, consumers seek cleaner labels and the presence of bioactive compounds because of their preventive claims [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%